Experimental Approach for the Validation of Odour Dispersion Modelling - L. Capelli; L. Dentoni; S. Sironi; J.M. Guillot (Chemical Engineering Transactions, 2012)
Different approaches can be adopted in order to validate the results of odour dispersion modelling. This paper describes the approach adopted for odour dispersion modelling considering the specific case of a MSW landfill located in Northern Italy. This work represents the first step of a more extended research project between Ecole des Mines d’Alès and Politecnico di Milano, which will study different approaches to evaluate the exposure to odours and odorous compounds.